Is there such a thing as free government data? - Federico Morando; Raimondo Iemma; Simone Basso (Internet Policy Review, 2013)
The recently-amended European Public Sector Information (PSI) Directive rests on the assumption that government data is a valuable input for the knowledge economy. As a default principle, the directive sets marginal costs as an upper bound for charging PSI. This article discusses the terms under which the 2013 consultation on the implementation of the PSI Directive addresses the calculation criteria for marginal costs, which are complex to define, especially for internet-based services. What is found is that the allowed answers of the consultation indirectly lead the responder to reason in terms of the average incremental cost of allowing reuse, instead of the marginal cost of reproduction, provision and dissemination. Moreover, marginal-cost pricing (or zero pricing) is expected to lead to economically efficient results, while aiming at recouping the average incremental cost of allowing re-use may lead to excessive fees.
Keywords: 300; Open data; Public sector information; EU Directive on the re-use of public sector information (PSI Directive); Price; charging; fees